Implementation of Rheumatology Health Care Transition Processes and Adaptations to Systems Under Stress: A Mixed‐Methods Study. Issue 3 (11th November 2022) - Chang, Joyce C.; Sears, Cora; Bitencourt, Nicole; Peterson, Rosemary; Alperin, Risa; Goh, Y. Ingrid; Overbury, Rebecca S.; Sadun, Rebecca; Smitherman, Emily; White, Patience H.; Lawson, Erica F.; Carandang, Kristine
Abstract : Objectives: Despite poor health care transition outcomes among young adults with pediatric rheumatic diseases, adoption of transition best practices is low. We sought to understand how structured transition processes were operationalized within pediatric rheumatology practices and what factors were perceived to enable adaptations during a global pandemic. Methods: We conducted a mixed methods study of team leaders' experiences during an interim analysis of a pilot project to implement transition policy discussions at sites in the Childhood Arthritis and Rheumatology Research Alliance Transition Learning Collaborative. We combined quantitative assessments of organizational readiness for change (9 sites) and semistructured interviews of team leaders (8 sites) using determinants in the Exploration, Preparation, Implementation, Sustainment Framework. Results: Engagement of nursing and institutional improvement efforts facilitated decisions to implement transition policies. Workflows incorporating educational processes by nonphysicians were perceived to be critical for success. When the pandemic disrupted contact with nonphysicians, capacity for automation using electronic medical record (EMR)–based tools was an important facilitator, but few sites could access these tools. Sites without EMR‐based tools did not progress despite reporting high organizational readiness to implement change at the clinic level. Lastly, educational processes were often superseded by acute issues, such that youth with greater medical/psychosocial complexity may not receive the intervention. Conclusion: We generated several considerations to guide implementation of transition processes within pediatric rheumatology from the perspectives of team leaders. Careful assessment of institutional and nursing support is advisable before conducting complex transition interventions. Ideally, new strategies would ensure interventions reach youth with high complexity.